Inter-phyla comparative genomics of plant pathogenic fungus reveals genomics similarity and copy number variations / Kenneth Tan Lee Shean - Kenneth Tan, Lee Shean (2014)

(untitled)
The impact of plant pathogenic fungus towards the industry of agriculture causes massive destruction of crops worldwide and thus stirring interest around the world for research in these plant pathogenic funguses. The vast development of sequencing technologies enabled many public efforts to decipher the genomics information about these funguses and example of such effort is the Fungal Genome Initiative (FGI) by Broad Institute. By using public genomics and annotation data from FGI for four different fungus species from two different phyla, inter-phyla comparative genomics between the fungus species revealed important common features of plant pathogenic funguses. Inter-Phyla comparative genomics results showed that there are 1,388 homologous protein-coding genes between Basidiomycota and Ascomycota. Also done was discovery of candidate protein-coding genes from both pathogen-host interaction-related genes and carbohydrate-active enzymes, which are known as protein-coding genes that are related to fungus pathogenicity. A total of 159 common candidate protein-coding PHI-base genes and 64 common candidate protein-coding genes for carbohydrate-active enzymes were identified between fungus from Basidiomycota and Ascomycota. Genes Copy Number Variation was also observed in both pathogenicity related genes discovery, with 5 candidate PHI-related genes and 3 candidates CAZy showed to have variation in terms of genes copy number. Also discovered is the significant difference in total number of pathogenicity genes between Ascomycetes and Basidiomycetes where Ascomycetes is found to have more copy number of pathogenicity-related genes thatn Basdiomycetes. This research could lead to development of broad-spectrum antifungal solution for the agricultural industry by targeting the common genes identified.